Double trouble: psychology and psychologization under the spotlight - Barnes, Brendon (PINS-Psychology in Society, 2017)
[BOOK REVIEW] De Vos, Jan (2013) Psychologization and the subject of late modernity. Houndmills: Palgrave Macmillan. ISBN 978-0-230-30846-6 hbk. Pages xi + 189. Jan de Vos’ starting point in the Psychologization and the subject of late modernity is the gap between being and knowledge. In other words, between how people are as psychological subjects and how they could be as psychologized subjects. He argues, as he has elsewhere, that psychologization is not simply a spillover of psychology into society but that psychology is psychologization. Psychologization is psychology’s paradigm.